Psychological dysfunction associated with calcaneal fractures. Issue 8 (August 2021) - Walsh, Tom P.; Vasudeva, Varun; Sampang, Kevin; Platt, Simon R.
Highlights: Psychopathology is significantly more prevalent in people sustaining a calcaneal fracture compared to an ankle fracture. Suicidal ideation was the only specific condition significantly more common in the calcaneal fracture group. The mechanism linking psychopathology to calcaneal fractures is unknown, but could be related to either conditions or medications (or both). Abstract: Introduction: The calcaneus is the most commonly fractured hindfoot bone, accounting for over 60% of all tarsal fractures. The aim of this study was to compare the mechanism of injury and psychological health status in patients presenting with calcaneal fractures to an age- and sex-matched control group with ankle fractures. Patients and methods: This retrospective study was undertaken within an orthopaedic unit at a tertiary hospital. An electronic medical record chart review was performed to identify eligible patients. Descriptive statistics were used to summarise the demographic and clinical characteristics of the patients. Between-group differences were analysed with the Mann-Whitney U test and Fisher's exact test for continuous and categorical variables, respectively. Multivariable binary logistic regression was used to determine the relationship between fracture type and underlying psychopathology, adjusting for mechanism of injury. Results: Two-hundred and fifteen patients met the eligibility criteria for calcaneal fractures and these patients were subsequently matched to 215 ankle fracture patients. Men accounted for 154 (71.6%) of the patients in each group. Over half (51.2%) of all calcaneal fractures were due to an uncontrolled fall above one-metre, as opposed to 26.0% of ankle fractures, p < 0.001. Falling from a standing height was more common in the ankle fracture group, 37 (17.2%) versus 10 (4.7%), p < 0.001. Patients with calcaneal fractures were more likely to have a diagnosed psychological health complaint, 63 (29.3%) versus 32 (14.9%), p < 0.001. Suicidal ideation was significantly more common in the calcaneal fracture group 14 (6.5%) versus 3 (1.4%), p  = 0.011. The presence of premorbid psychopathology was associated with calcaneal fracture, after adjusting for mechanism of injury (odds ratio 2.20, 95% confidence interval 1.32 to 3.65, p  = 0.003). Conclusion: Calcaneal and ankle fractures display differences in both the mechanism of injury and the history of psychological health conditions. However, after adjusting for the mechanism of injury, diagnosed premorbid psychopathology remains twice as likely in someone with a calcaneal fracture as opposed to an ankle fracture. It may be prudent for orthopaedic surgeons to consider further investigations of psychological health when managing patients with a calcaneal fracture.